Native Fluorescent Natural Deep Eutectic Solvents for Green Sensing Applications: Curcuminoids in Curcuma longa Powder - Lorenzetti, Anabela Silvana (2021)
Natural deep eutectic solvents are a trending topic in Green Chemistry. These solvents present high solubilization capacity, reusability, tunable properties, simple preparation, biodegradability, safety, high availability, and low cost, making them excellent candidates for analytical applications. In this work, a new family of fluorescent eutectic systems is described, with the fluorescence property being unknown and unused so far. For this purpose, a novel preparation method using an ultrasound probe was employed, by means of an innovative single-step procedure, that included the preparation of FCH (fructose, citric acid, and water, 1:1:5 molar ratio) and the extraction/determination of curcuminoids from Curcuma longa powder. This methodology was successfully carried out by employing a portable and inexpensive 3D-printed fluorometer and a smartphone. In this way, extraction efficiencies between 90 and 106%, relative to the NIST reference method, were obtained in just 3.40 min. Besides, the greenness of the new methodology was evaluated by employing the AGREE metric, showing that the developed approach is >2.5 times greener than previously published works for curcuminoid determination. This groundbreaking procedure is robust, versatile, and simple to implement, does not require sophisticated apparatus or instruments in the detection step, and, mainly, agrees with Green Analytical Chemistry (GAC) principles.